2014
DOI: 10.1155/2014/317259
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Automatic Negative Thoughts, and Unconditional Self-Acceptance in Rheumatoid Arthritis: A Preliminary Study

Abstract: Objectives. This research was carried out in two stages: the objectives of the first stage were (1) to identify the existing relationships between the level of anxiety, the frequency of automatic negative thoughts, and unconditional self-acceptance and (2) to capture the existing differences regarding these variables between people diagnosed with rheumatoid arthritis and those with no such medical history. Methods. The sample made up of 50 subjects filled out the following three questionnaires: the Hamilton A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
1
10
0
4
Order By: Relevance
“…A substantial portion of CBT’s effectiveness for pain management is likely attributable to its emphasis on cognitive skills (e.g., cognitive restructuring, distraction, etc.) that can be honed through practice and deployed to manage daily pain symptoms (44, 45). It is important to note that the present trial enrolled only high-catastrophizing patients, and there is some recent evidence suggesting that the highest-catastrophizing patients may benefit most from these cognitive coping skills (46).…”
Section: Discussionmentioning
confidence: 99%
“…A substantial portion of CBT’s effectiveness for pain management is likely attributable to its emphasis on cognitive skills (e.g., cognitive restructuring, distraction, etc.) that can be honed through practice and deployed to manage daily pain symptoms (44, 45). It is important to note that the present trial enrolled only high-catastrophizing patients, and there is some recent evidence suggesting that the highest-catastrophizing patients may benefit most from these cognitive coping skills (46).…”
Section: Discussionmentioning
confidence: 99%
“…Since a complex interplay is known among the factors determining damage accrual in RA and the disability has been traditionally attributed to joint damage, a predictive role of psychological and social factors, which are very different between cultures and races, is gaining recognition [ 6 ]. Interestingly, it has been suggested that the effect of some psychological aspects of RA may shift in favor of the patient as the disease progresses and the individual learns to adapt better [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This tranquillity fosters self-awareness (Bruce and Davies 2005), self-acceptance (Carson 2006), self-compassion (Hoge et al 2013, Raab 2014, non-dualistic views (Gill et al 2015), and forgiveness (Webb et al 2013) due to a complex of neurophysiological mechanisms (Jerath et al 2012, Vago andSilbersweig 2012). These internal resources positively correlate with physical health (Lawler et al 2005) and psychological well-being (Germer and Neff 2013, Krause and Ellison 2003, Palos and Vîscu 2014. Thus, mindfulness training is proposed to death-related service practitioners (Cacciatore et al 2015) (for example, grief and bereavement, palliative and hospice care) and their clients in order to empower themselves to enhance mental wellness.…”
Section: Discussionmentioning
confidence: 99%